2011
DOI: 10.1038/leu.2011.202
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal mutation of RUNX1 attenuates the DNA-damage repair response in hematopoietic stem cells

Abstract: Loss-of-function mutations of RUNX1 have been found in acute myeloid leukemia (AML) and myelodysplastic syndromes (MDSs). Although several reports have suggested roles for RUNX1 as a tumor suppressor, its precise function remains unknown. Because gene alterations of RUNX1 by themselves do not lead to the development of leukemia in mouse models, additional mutation(s) would be required for leukemia development. Here, we report that the C-terminal deletion mutant of RUNX1, RUNX1dC, attenuates DNA-damage repair r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 38 publications
(41 reference statements)
2
29
0
Order By: Relevance
“…42 Likewise, RUNX1 and p53 synergistically activate the transcription of GADD45A, encoding a sensor of DNA stress, and MDS/AML patients with mutated RUNX1 show decreased GADD45A expression. 43 These observations are further corroborated by the inability of RUNX1 to induce cellular senescence in murine fibroblasts with defective p53. 44 The role of HLTF in genome maintenance and its intimate relationship with RUNX1 raise the possibility that a RUNX1/HLTF axis may collaborate with p53 in AML leukemogenesis.…”
Section: Discussionsupporting
confidence: 64%
“…42 Likewise, RUNX1 and p53 synergistically activate the transcription of GADD45A, encoding a sensor of DNA stress, and MDS/AML patients with mutated RUNX1 show decreased GADD45A expression. 43 These observations are further corroborated by the inability of RUNX1 to induce cellular senescence in murine fibroblasts with defective p53. 44 The role of HLTF in genome maintenance and its intimate relationship with RUNX1 raise the possibility that a RUNX1/HLTF axis may collaborate with p53 in AML leukemogenesis.…”
Section: Discussionsupporting
confidence: 64%
“…Most mutations occur in the N-terminal region. Mutations affecting the C-terminal part of RUNX1 attenuate the DNA-damage repair response in hematopoietic stem cells [35]. RUNX1 deficiency results in a reduced ribosome biosynthesis, attenuated unfolding protein response, a reduced metabolic profile, lower p53 levels and decreased apoptosis, in line with a model of RUNX1 loss-of-function mutations generating genotoxic stress-resistant hematopoietic stem cells that outcompete normal HSPC [36].…”
Section:  Functional Properties Of Runx1mentioning
confidence: 73%
“…Next, we investigated why mutation of CDC25C is a frequent genetic event in FPD/AML. It is known that RUNX1 mutations suppress DNA damage repair and subsequent cell cycle arrest in hematopoietic cells by means of transcriptional suppression of several genes that are involved in DNA repair 12,13 . We confirmed that FPD/AML-associated RUNX1 mutations have similar effects, as we observed activation of the G2/M checkpoint mechanism in the presence of RUNX1 mutations ( Fig.…”
Section: Resultsmentioning
confidence: 99%